Development of functionalized hollow microporous organic capsules encapsulating morphine – an in vitro and in vivo study. Issue 4 (3rd January 2017) - Razzaque, Shumaila; Cai, Chen; Lu, Qun-Wei; Huang, Feng-Zhen; Li, Yu-Sang; Tang, He-Bin; Hussain, Irshad; Tan, Bien
Abstract : Carboxylic group functionalized hollow microporous organic capsules (HMOCs) are synthesized that show extraordinary high encapsulation efficiency of morphine·HCl and its promising prolonged release. Abstract : Microporous organic capsules with hollow interiors have received enormous attention due to their unusual encapsulation efficiency to confine chemicals within their hollow cavities and prompted controlled release by circumventing their ripening or poisoning. To this end, herein, we report the design and synthesis of carboxylic group functionalized hollow microporous organic capsules (HMOCs) using a facile emulsion polymerization technique that show extraordinary high encapsulation efficiency (up to 98%) of morphine·HCl and its promising prolonged release. The functionalized HMOCs are found to release the drug at a rate which is proportional to the amount of drug remaining in its interior. Due to the presence of hollow and porous morphologies, they possess high BET surface areas, i.e. up to 974 m 2 g −1 . Moreover, the in vivo results showed that functionalized HMOCs can offer slow release of active drug molecules and attenuate the level of writhing response over 72 h of intraperitoneal injection. The functionalized HMOCs, therefore, present a new class of potential drug delivery systems that can maintain the slow and prolonged release of analgesics by lowering the dosage and avoid frequent administration.